Tradição literária mato-grossense : a natureza na poesia produzida por sacerdotes no século XX - Santos, Michael Jhonatan Sousa (2021)
This thesis investigates and reveals a literary tradition of Mato Grosso, founded on poetic images of nature, which interconnects the works of Dom Francisco de Aquino Corrêa, Fr. Antônio Rodrigues Pimentel and Dom Pedro Casaldáliga, throughout the 20th century. In order to do that, it highlights the structuring process of the analyzed poems, exposing the tradition through textual, historical and social data, without losing sight of the unique character of each writer. In Aquino's work, from the beginning of the century, we highlight the poetic and ideological encounter of times (BOSI, 1977), with emphasis on the relations of negativity and positivity that Aquino's poetry establishes with the dominant ideology. As of 1964, the product of these relations is refined by Pimentel, who amplifies the negative factor and uses it, as well as other data from Cuiabá and Mato Grosso culture, as a poetic element of resistance in the setting of a conflict between tradition and modernity. Considered from 1971 onwards, Casaldáliga's poetry is connected to that of other writers through three axes of textual similarities, indicative of Mato Grosso literary tradition. The first occurs because the structure of the poems absorbs a similar socioeconomic and political situation; the second comes from the structural absorption of common cultural assumptions; and the third concerns the linguistic coincidences concerning the construction of certain poetic images of nature, which go beyond the fortuitous character when they are substantiated by at least one of the first two axes. Methodologically, we use the concept of literary tradition, in Antonio Candido (2000), combined with that of intertextuality, in Kristeva (2005) and Jenny (1979), mobilized in accordance with the notes on comparative literature by Nitrini (2015). For formal analysis, we employed the Strata-Model in the scope of the phenomenology of literary work, according to Ramos (2011). In this manner, the work allows the recognition of factors external to itself that cooperated in its configuration; among them, the research highlighted, primarily, those referring to the culture and history of Mato Grosso, and those of an existential nature, considered from the perspective of Heidegger (1992, 1998, 1999), Agostinho (2002) and Derrida (1973).